Effects of starvation for potassium and other inorganic ions on protein degradation and ribonucleic acid synthesis in Escherichia coli. - St John, A C (1980)
Starvation of Escherichia coli for potassium, phosphate, or magnesium ions leads to a reversible increase in the rate of protein degradation and an inhibition of ribonucleic acid (RNA) synthesis. In cells deprived of potassium, the breakdown of the more stable cell proteins increased two- to threefold, whereas the hydrolysis of short-lived proteins, both normal ones and analog-containing polypeptides, did not change. The mechanisms initiating the enhancement of proteolysis during starvation for these ions were examined. Upon starvation for amino acids or amino acyl-transfer RNA (tRNA), protein breakdown increases in relA+ (but not relA) cells as a result of the rapid synthesis of guanosine-5'-diphosphate-3'-diphosphate (ppGpp). However, a lack of amino acyl-tRNA does not appear to be responsible for the increased protein breakdown in cells starved for inorganic ions, since protein breakdown increased in the absence of these ions in both relA+ and relA cultures, and since a large excess of amino acids did not affect this response. In bacteria in which energy production is restricted, ppGpp levels also rise, and protein breakdown increases. The ion-deprived cultures did show a 40 to 75% reduction in adenosine-5'-triphosphate levels,l similar to that seen upon glucose starvation. However, this decrease in ATP content does not appear to cause the increase in protein breakdown or lead to an accumulation of ppGpp. No consistent change in intracellular ppGpp levels was found in relA+ or relA cells starved for these ions. In addition, in relX mutants, removal of these ions led to accelerated protein degradation even though relX cells are unable to increase ppGpp levels or proteolysis when deprived of a carbon source. In the potassium-, phosphate-, and magnesium-deprived cultures, the addition of choramphenicol or tetracycline caused a reduction in protein breakdown toward basal levels. Such findings, however, do not indicate that protein synthesis is essential for the enhancement of protein degradation, since blockage of protein synthesis by inactivation of a temperature-sensitive valyl-tRNA synthetase did not restore protein catabolism to basal levels. These various results and related studies suggest that the mechanism for increased protein catabolism on starvation for inorganic ions differs from that occurring upon amino acid or arbon deprivation and probably involves an enhanced susceptibility of various cell proteins (especially ribosomal proteins) to proteolysis.